Responses of Cowpea Genotypes to Arbuscular Mycorrhiza - Rohyadi, Agus; Noviani, Rina; Isnaini, Mulat (AGRIVITA, Journal of Agricultural Science, 2017)
A pot experiment was conducted under glasshouse conditions to evaluate response of some cowpea genotypes to Arbuscular Mycorrhiza. It was a 2 x 6 factorial experiment comprising factors of mycorrhizal inoculation (M) with AM fungal inoculum (M1) and without AM fungal inoculum (M0), and of plant genotypes (G) with Gf (a cowpea inbred line), Gm (a mung bean inbred line), Gh1, Gh2, Gh3 and Gh4 (the 1st, 2sd, 3rd and 4th generation of cowpea hybrids, derived from cross-breeding Gf x Gm as female and male parents, respectively), and arranged in a completely randomized design with 9 replicated pots, where plants were grown up for 14, 28 and 42 days before harvested serially. Responses of cowpea genotypes to colonization and contribution of mycorrrhizal symbiosis varied greatly. The intensity of plant roots colonized by mycorrhizal fungi was highest on Gf, and it was descent on the cowpea hybrids following their generation order. On the other hand, the highest in plant growth response to mycorrhizal function was on Gm, followed by Gh1 and Gh2. These results indicated that the cross-breed of cowpea and mung bean lines has generated cowpea hybrids that tend to benefit less from mycorrhizal symbiosis for their growth.